THU0333 CARDIOVASCULAR COMORBIDITIES ARE COMMON IN RHEUMATOID ARTHRITIS PATIENTS WHO PRACTICE LESS PHYSICAL ACTIVITY AND WHO HAVE WORSE FUNCTIONAL CAPACITY. (2nd June 2020) - Pereira, I.; Ribas, G.; Castro, G.; Castelar, G.; Vargas-Santos, A. B.; Albuquerque, C.; Gomides, A. P.; Bertolo, M.; Louzada Jr, P.; Giorgi, R.; Guimarães, M. F.; Radominsky, S.; et al.
Abstract : Background: Patients with rheumatoid arthritis have more cardiovascular comorbidities which contributes to hospitalization and mortality. Objectives: This study aims to investigate whether there is an association between cardiovascular comorbidities in RA with subgroup of patients and clinical findings of the disease Methods: This study is a cross-sectional part of Rheumatoid Arthritis in Real Life (REAL), which is a multicenter prospective study conducted in Brazil, involving 13 centers specialized in the care of patients with RA. All subjects met the ARA (1987) or ACR/EULAR (2010) RA classification criteria. Subjects were submitted to clinical interview with physical exam and review of medical records. A sample of 1116 patients was selected for convenience. The association between cardiovascular comorbidities (systemic arterial hypertension (HA), diabetes mellitus (DM) type2, dyslipidemia, stroke and heart failure), the clinical characteristics and laboratory parameters of RA was evaluated through chi-square hypothesis tests, Student`s t-test, Fischer exact test, correlations test and ANOVA. Also, correction Bonferoni test was used for multiple comparisons. Differences were considered statistically significant only when p ≤ 0.05. Results: 89% of the patients were female, with a mean age of 58 years. 62% of patients with RA had comorbidities, with HA the most prevalent. There were statistically significant association between cardiovascular comorbidities with age (61.71±9.69years old vs 53.03±12.10) (p <0.001), lower educational level (n=282±66.5vs 143±33, 5) (p <0.001), lower physical activity (n=132±73.3 vs 48±26.7) (p <0.001), disease duration (18.5±9.75 years vs 14.4±8.61) (p <0.001), positive anti-CCP test (60.5% vs 39.5%) (p = 0.027), high clinical disease activity index CDAI) (65.9%vs 34.1%) (p <0.001), DAS28VHS (3.72±1.46 vs 3.45±1.58) (p = 0.008) and HAQ score (1.00±0.76) vs 0.83±0.77 (p <0.001). Conclusion: The frequency of cardiovascular comorbidities is high in RA patients and is associated with age, disease duration and positive anti-CCP test. It is also important to see that these comorbidities are more common in patients with lower frequency of physical activity and lower functional capacity, higher disease activity score and lower level of education. Better control of disease activity and extensive information to patients about the importance of exercise should be parallel objectives in RA. Disclosure of Interests: Ivanio Pereira Grant/research support from: Has received consulting fees, speaking fees and supporting for internationals congresses from Roche, Pfizer, UCB Pharma, Eli-Lilly, Abbvie and Janssen, Consultant of: Has received consulting fees, speaking fees and supporting for internationals congresses from Roche, Pfizer, UCB Pharma, Eli-Lilly, Abbvie and Janssen, Paid instructor for: Has received consulting fees, speaking fees and supporting for internationals congresses from Roche, Pfizer, UCB Pharma, Eli-Lilly, Abbvie and Janssen, Speakers bureau: Has received consulting fees, speaking fees and supporting for internationals congresses from Roche, Pfizer, UCB Pharma, Eli-Lilly, Abbvie and Janssen, Gabriela Ribas: None declared, G Castro: None declared, Geraldo Castelar Grant/research support from:: Has received consulting fees from AbbVie, Bristol-Myers Squibb, Eli Lilly, Glaxosmithkline, Janssen, Pfizer, Sanofi Genzyme and Roche, Consultant of:: Has received consulting fees from AbbVie, Bristol-Myers Squibb, Eli Lilly, Glaxosmithkline, Janssen, Pfizer, Sanofi Genzyme and Roche, Paid instructor for:: Has received consulting fees from AbbVie, Bristol-Myers Squibb, Eli Lilly, Glaxosmithkline, Janssen, Pfizer, Sanofi Genzyme and Roche, Speakers bureau:: Has received consulting fees from AbbVie, Bristol-Myers Squibb, Eli Lilly, Glaxosmithkline, Janssen, Pfizer, Sanofi Genzyme and Roche, Ana Beatriz Vargas-Santos Grant/research support from: Has received supporting for international medical events from AbbVie and Janssen, Cleandro Albuquerque Grant/research support from: Has received personal fees and/or non-financial support from Pfizer, AbbVie, AstraZeneca, Janssen, Bristol-Myers Squibb, Roche, Novartis and UCB, Consultant of: Has received personal fees and/or non-financial support from Pfizer, AbbVie, AstraZeneca, Janssen, Bristol-Myers Squibb, Roche, Novartis and UCB, Paid instructor for: Has received personal fees and/or non-financial support from Pfizer, AbbVie, AstraZeneca, Janssen, Bristol-Myers Squibb, Roche, Novartis and UCB, Speakers bureau: Has received personal fees and/or non-financial support from Pfizer, AbbVie, AstraZeneca, Janssen, Bristol-Myers Squibb, Roche, Novartis and UCB, Ana Paula Gomides Consultant of: Abvvie, Manoel Bertolo Grant/research support from: Has participated in clinical and/or experimental studies related to this work and sponsored by Roche; has delivered speeches at events related to this work and sponsored by AbbVie and Pfizer, Paid instructor for: Has participated in clinical and/or experimental studies related to this work and sponsored by Roche; has delivered speeches at events related to this work and sponsored by AbbVie and Pfizer, Speakers bureau: Has participated in clinical and/or experimental studies related to this work and sponsored by Roche; has delivered speeches at events related to this work and sponsored by AbbVie and Pfizer, Paulo Louzada Jr Grant/research support from: Has received supporting for internationals congresses from Bristol-Myers Squibb, UCB and consulting fees from Pfizer, Paid instructor for: Has received supporting for internationals congresses from Bristol-Myers Squibb, UCB and consulting fees from Pfizer, Speakers bureau: Has received supporting for internationals congresses from Bristol-Myers Squibb, UCB and consulting fees from Pfizer, Rina Giorgi: None declared, Maria Fernanda Guimarães: None declared, Sebastião Radominsky Grant/research support from: Has received consulting and speaking fees from Abbvie, Janssen, Pfizer, Roche and UCB, Consultant of: Has received consulting and speaking fees from Abbvie, Janssen, Pfizer, Roche and UCB, Paid instructor for: Has received consulting and speaking fees from Abbvie, Janssen, Pfizer, Roche and UCB, Speakers bureau: Has received consulting and speaking fees from Abbvie, Janssen, Pfizer, Roche and UCB, Karina Bonfiglioli Consultant of: Roche, Abbvie, Pfizer, Janssen and BMS, Maria de Fátima Sauma: None declared, Claiton Brenol: None declared, Evandro Coutinho: None declared, Licia Mota Grant/research support from: Has received personal or institutional support from AbbVie, Janssen, Pfizer and Roche; has delivered speeches at events related to this work and sponsored by AbbVie, Janssen, Pfizer, Roche and UCB., Speakers bureau: Has received personal or institutional support from AbbVie, Janssen, Pfizer and Roche; has delivered speeches at events related to this work and sponsored by AbbVie, Janssen, Pfizer, Roche and UCB.